Pupils Show Off Inventions - New Straits Times, news@nst.com.my (2008)
Little minds are at work at the three-day 19th International Invention Innovation Technology Exhibition (ITEX08) with 10 and 11-year-olds in the running for the grand prize for creative inventions in the primary school category where five teams are competing.